Design and finite element analysis of interference press-fit aluminium nut - Abdullah, Aznizam (2014)
Construction of mechanical platforms requires a suitable method for assembling two physical components. One of the assembly methods that are being used for discrete hardware component is called fasteners. In the world of Technical Vocational Education Training (TVET), some projects require students to design and produce a product that will involve the installation of mechanical components. Taking into account the difficulties faced to make such assembly, joining process involved cutting the parts accurately until the components could be mated together. Thus, the fastener innovation was rather innovated to provide a more effective alternative method. The Interference Press-fit Aluminum Nut (INPREANUT) has designed and manufactured to meet such purpose. Quality Function Deployment (QFD) is used to translate the user needs and requirements into technical requirements. Once this step is completed, Design for Manufacturing and Assembly (DFMA) is used to select the best approach in assembly to reduce the constraints such as assembly time, efficiency and most importantly, cost. During the design process of INPREANUT, the strength of the connection between INPREANUT with aluminum round tube was analyzed using Finite Element Analysis (FEA). The CA TIA 3D software was employed to design INPREANUT being imported into ANSYS software to analyse the INPREANUT' s shear strength. The strength of a mechanical connectivity is a key requirement to ensure that it has the expected friction force as well able to meet some of the other features. The features are easy to install, safe, lightweight, saves time and accurate. After completing the preliminary design and analysis, the INPREANUT is then fabricated and experiments performed to verify that the numerical methods used correlates with real measurement values. It is hoped that the INPREANUT fabrication will able to help students to make mechanical assembly components quickly, accurately and economically.